Management of a ruptured epidural catheter, an anesthesiologist’s dilemma: a case report - Mendoza-Aceves, Rodrigo A.; Banegas-Ruiz, Rodrigo; Gómez-Mendoza, Francisco F.; Román-Hernández, Rigoberto R.; Aguirre-Ramírez, Jesica A.; León, Jesica K. R. C.; Coronado, Paola G. G.; Torres, Juan P. E.; Alcazar-Castro, Javier; Caprielova, Yuri J.; Hernández Arteaga, Leonel D.; Llergo, Román A. R.; et al. (International Journal of Research in Medical Sciences, 2020)
Epidural anesthesia is a widely used anesthetic technique in lower extremity surgeries although it is a relatively safe procedure, it can have complications, such as rupture of the epidural catheter. This is a 69-year-old male patient with a diagnosis of Wagner IV diabetic foot is presented, which was scheduled for left supracondylar amputation in which after epidural block, retention of the catheter tip in the epidural space at level L2-L3 was seen, so hemi laminectomy was performed in a second surgical stage in L2 and removal of the epidural catheter. Ideally a broken needle should be removed as soon as possible.